Assessment of The Technical Efficiency and Cost and Returns on Seed Yam Farms in North-Central - Morolake Bolaji; Raphael Olarenwaju Babatunde; Olubunmi Abayomi Omotesho (International Journal on Food, Agriculture and Natural Resources, 2023)
Achieving maximum output with a minimum level of resources has been a major discourse in recent years mostly in Nigeria’s seed yam production. Thus, the study evaluated the technical efficiency of the CAY- and NRCRI - seed yam farm and the costs and returns to seed yam production of CAY- and NRCRI - seed yam farms. The study adopted a quantitative research approach. Similarly, a multistage sampling method was used to 283 seed yam farmers. Descriptive statistics, cobb douglas stochastic frontier production function model and gross margin analysis were used for the study. The findings of the study revealed that technical efficiency scores of CAY- (20%) and NRCRI (17%) – seed yam farmers were generally low respectively, Similarly, CAY-Seed yam farmers’ farms had a higher gross margin ($199.64) when compared to NRCRI seed yam farmers’ farms ($97.29), The study concludes that seed yam technologies did not generally improve the technical efficiency of the seed yam farms. The study recommends that external factors such as seed yam varieties used should be assessed. For instance, farmers’ compliance to technologies introduced and the state of health of seed yam farmers should be considered in determining the technical efficiency of farms.